2016
DOI: 10.1136/esmoopen-2016-000091
|View full text |Cite
|
Sign up to set email alerts
|

Renal insufficiency and cancer treatments

Abstract: Renal insufficiency has been shown to be highly prevalent in patients with cancer. This renal insufficiency has been reported to be associated with reduced overall survival and increased cancer-related mortality. Therefore, it is important to screen patients with cancer for renal insufficiency, using an adequate and reliable method of estimation of the renal function. Renal insufficiency may influence 1 or several of the 4 pharmacokinetic phases (absorption, distribution, metabolism, elimination/excretion), po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 30 publications
5
60
0
Order By: Relevance
“…Estimation of renal function is important since renal insufficiency is directly associated with increased mortality after cancer [43]. To explore the effect of renal function on prognosis, we also analyzed the association of serum Cys-C, CRE and e-GFR with the prognosis of RCC patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of renal function is important since renal insufficiency is directly associated with increased mortality after cancer [43]. To explore the effect of renal function on prognosis, we also analyzed the association of serum Cys-C, CRE and e-GFR with the prognosis of RCC patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, bevacizumab and gemcitabine may cause vascular lesions, while platinum salts, methotrexate, cetuximab and vincristine expose patients to tubulo-interstitial lesions (25). RF was reported to be associated with reduced overall survival and increased mortality in cancer patients (26). In our study, advanced age, male gender, HIV infection, severity of RF and low hemoglobin level (<8 g/dL) were the risk factors for death.…”
Section: Discussionmentioning
confidence: 47%
“…For instance, the use of serum creatinine as a measure of GFR in patients with cancer may be influenced by poor dietary intake of protein, muscle wasting, malnutrition, changes in hydration, and liver disease that are prevalent in these patients (1). As an example of this, Launay-Vacher and colleagues (9,10) found that an abnormal serum creatinine was seen in ,10% of patients with cancer, whereas an abnormal GFR was seen in a much higher percentage (approximately 50%). In fact, it may be the case that patients with cancer more often present with abnormal GFRs than normal levels of kidney function.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it may be the case that patients with cancer more often present with abnormal GFRs than normal levels of kidney function. For instance, only 38.6% of patients with breast cancer, 38.9% of patients with lung cancer, 38.3% of patients with prostate cancer, 27.5% of patients with gynecologic cancer, and 27.2% of patients with colorectal cancer had a GFR$90 ml/min per 1.73 m 2 at the time of therapy initiation (9,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%